Performance Evaluation and Empirical Study of the E-commerce Service Industry: A Case Study of the Yangtze River Delta in China - Dongqing Luan, Xiaozhen Hao, Zhijie Xia, Zongwei Li (Forest Chemicals Review)
The e-commerce service industry is an emerging industry with the development of e-commerce. In this paper, the DEA method is used to evaluate the performance of the e-commerce service industry in the Yangtze River Delta region, and then the Tobit regression model is adopted to evaluate the correlation between the e-commerce service industry and various factors. The study shows that the indicator GDP per capita as an economic factor and value added of the tertiary sector, post and telecommunications volume, the R&D investments as comprehensive factors as influencing factors positively with the level of the e-commerce service industry. Among them, economic factors have a deeper impact on the development of the e-commerce service industry.